1998
DOI: 10.1002/(sici)1096-9896(199808)185:4<366::aid-path122>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Fractal characterization of chromatin appearance for diagnosis in breast cytology

Abstract: This study explores the use of fractal analysis in the numerical description of chromatin appearance in breast cytology. Images of nuclei from fine‐needle aspiration biopsies of the breast are characterized in terms of their Minkowski and spectral fractal dimensions, for 19 patients with benign epithelial cell lesions and 22 with invasive ductal carcinomas. Chromatin appearance in breast epithelial cell nuclear images is demonstrated to be fractal, suggesting that the three‐dimensional chromatin structure in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Pathologists have proposed the fractal dimension of nuclear chromatin as a prognostic factor in some tumors, such as lymphoblastic leukemia (91), myelodysplastic syndromes (92) and laryngeal carcinoma (93). This is a promising method that may estimate patients' outcome early on a cytological fine-needle aspirate, since it has also been used for fine-needle aspirates from breast cytology (94). Recent data suggest that this technique may be applied to thyroid and possibly be useful in predicting aggressiveness (95).…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…Pathologists have proposed the fractal dimension of nuclear chromatin as a prognostic factor in some tumors, such as lymphoblastic leukemia (91), myelodysplastic syndromes (92) and laryngeal carcinoma (93). This is a promising method that may estimate patients' outcome early on a cytological fine-needle aspirate, since it has also been used for fine-needle aspirates from breast cytology (94). Recent data suggest that this technique may be applied to thyroid and possibly be useful in predicting aggressiveness (95).…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…This was one of the reasons which encouraged NN as the most widely used classification algorithm in various biomedicine and healthcare fields [44,45,46]. For example, NN has been widely used as the algorithm supporting the diagnosis of diseases including cancers [47][48][49][50][51] and predict outcomes [52][53][54]. In NN, basic elements are neurons or nodes.…”
Section: Neural Network (Nn)mentioning
confidence: 99%
“…6 As a result, we set the values of the parameters as follows: the grid size is 4, the node threshold is 0.50, the link exponent is 4.4, and the number of hidden units is 12.…”
Section: Parameter Selection By Cross-validationmentioning
confidence: 99%
“…Another subset of these studies uses fractals that describe the similarity levels of different structures found in a tissue image over a range of scales [6], [9]. These studies use the fractal dimensions as their features and use the k-nearest neighborhood algorithm [9], neural networks, and logistic regression [6] as their classifiers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation